Comparative Analysis of Analytical and Numerical Methods on the Safety Factor of Retaining Walls - Akbar, Aulia; Wibowo, Tommy Prasetyo; Wulandari, Tika Ermita (Kadiri University, 2024)
The stability of retaining walls is a major concern in geotechnical design, especially in landslide-prone areas such as Indonesia. A comprehensive analysis requires an in-depth understanding of the failure mechanism and the factors that influence its stability. Therefore, a comparison of various analytical and numerical methods in the stability of retaining walls is an important step to determine the most effective approach. The data were collected through laboratory tests and field investigations of soil properties. The retaining wall design was modeled using Plaxis and Midas software. The analysis focused on comparing the safety factor values obtained from the Rankine method with those derived from Plaxis and Midas simulations. The results show that Rankine provides a high safety factor, namely 2.54 for rotation and 2.447 for shear. Rankine, although simple, remains relevant for uniform soil conditions. Plaxis can provide more detailed deformation and pressure distribution predictions with a safety factor reaching 2.95 in the third excavation stage. Meanwhile, Midas provides a comprehensive analysis of axial force and bending moment with a safety factor value that tends to be smaller. This study provides new insights into how each method can be used effectively for different technical conditions, and provides practical guidelines for geotechnical planners in choosing the appropriate analysis method to improve the efficiency and safety of retaining wall design.